Psychosocial and financial impact of disease among patients of dermatophytosis, a questionnaire-based observational study - Nayankumar H Patel; Jignaben K Padhiyar; Ani P Patel; Aseem S Chhebber; Bhagirath R Patel; Tejas D Patel (Wolters Kluwer Medknow Publications, 2020)
Introduction: In the present epidemic of chronic, recalcitrant, and widespread dermatophytosis, impact of disease on quality of life (QoL) can be severe. Similarly, financial impact due to treatment cost and loss of wages needs consideration too. Aims and Objectives: Our primary aim was to evaluate the impact of dermatophytosis on QoL and the financial burden on individual and family. Materials and Methods: Adult patients having dermatophytosis were included in the study. Standard Dermatology Life Quality Index (DLQI) questionnaire was used to evaluate the psychosocial impact, and financial burden was evaluated by nine binary questions. Results: A total of completed 299 DLQI surveys and 275 financial burden surveys were taken for final analysis. Mean DLQI was 12.25 (SD = 5.56, n = 299). Significant association between total body surface area (BSA) and DLQI score was observed (rs= 0.251,P <0.001, n = 299). Presence of tinea corporis was found to be significantly affecting the choice of clothing (P = 0.018, χ2 = 5.127, CI 95%). More numbers of male respondents reported loss of work or study hours due to their illness (P = 0.015, χ2 = 5.196, CI 95%), which was significantly associated with the BSA involved (P < 0.05, t = 5.529, CI 95%). Some difficulties in sexual activity were reported by 35.6% patients, which has significant association with tinea cruris (P = 0.001, χ2 = 10.810, CI 95%). Median household income was 10,000 INR and interquartile range (IQR) being 8,000-19,000. Mean financial burden calculated at 3.458 (SD = 1.696, n = 275), whereas mean financial worry reported by patient stood at 3.661 (SD = 1.216, n = 275). Financial burden showed significant correlation with "previous treatment approximate cost," financial worry, and DLQI (P < 0.05, CI 95%). Financial worry (P = 0.016, rs= 0.145, CI 95%) and financial burden (P = 0.002, rs- = 0.145, CI 95%) both showed positive correlation with duration of disease. Conclusion: In present scenario of Dermatophytosis in India, the disease and its treatment causing impact on QOL as well as on personal financial burden and worry need consideration.